Level of self-efficacy of middle school students during the Covid-19 pandemic - Taufik Agung Pranowo (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2021)
Purpose - The purpose of this study was to determine the level of self-efficacy in students at Sarbini Islamic Junior High School. Method - This type of research is quantitative research. The population in this study was 215 students. The sample used in this study was 25 students. Sampling was done by purposive random sampling. Data analysis in this study used descriptive quantitative.Result - The level of student self-efficacy at the moderate level shows a value of 26%. As for the high level shows a value of 21%. Students at Sarbini Islamic Junior High School experienced a low level of self-efficacy with a value of 7%, and a level of self-efficacy in the less category with a value of 19%. In each indicator, it can be seen that there are only 2 levels of high self-efficacy with values of 77 and 81 on the indicators of Adjusting to Tasks and Self-Assessment of Ability to Do Tasks. While other indicators are in the medium category.Implications – This research has an impact on knowing the level of self-efficacy of Sarbini Islamic Junior High School students to provide an overview to Sarbini Islamic Junior High School teachers in the learning process.Originality – Strengthening students at Islamic Junior High School through self-efficacy in the form of guidance and counseling services.***Tujuan - Tujuan dari penelitian ini adalah untuk mengetahui tingkat efikasi diri pada siswa SMP Islam Sarbini.Metode - Jenis penelitian ini adalah penelitian kuantitatif. Populasi dalam penelitian ini adalah 215 siswa. Sampel yang digunakan dalam penelitian ini sebanyak 25 siswa. Pengambilan sampel dilakukan secara purposive random sampling. Analisis data dalam penelitian ini menggunakan deskriptif kuantitatif.Hasil - Tingkat efikasi diri siswa pada tingkat sedang menunjukkan nilai sebesar 26%. Sedangkan untuk level tinggi menunjukkan nilai sebesar 21%. Siswa SMP Islam Sarbini mengalami tingkat efikasi diri rendah dengan nilai 7%, dan tingkat efikasi diri dalam kategori kurang dengan nilai 19%. Pada masing-masing indikator terlihat hanya terdapat 2 tingkat efikasi diri yang tinggi dengan nilai 77 dan 81 pada indikator Menyesuaikan Tugas dan Penilaian Diri Kemampuan Mengerjakan Tugas. Sedangkan indikator lainnya berada pada kategori sedang.Implikasi - Penelitian ini berdampak pada mengetahui tingkat efikasi diri siswa SMP Islam Sarbini untuk memberikan gambaran kepada guru SMP Islam Sarbini dalam proses pembelajaran.Originalitas - Penguatan siswa MTs melalui studi level efikasi diri berupa layanan bimbingan dan konseling.